Gravitational body forces focus North American intraplate earthquakes - Will Levandowski (Nature Portfolio, 2017)
Intraplate earthquakes occur far from tectonic plate boundaries and so it is vital to understand how and where they may happen. Here, Levandowskiet al. create a 3D density map of the North America Great Plains showing that gravitational forces play a controlling role in intraplate earthquake locations.